2012
DOI: 10.1093/rheumatology/ker400
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptors and their detection of nuclear self-antigen leading to immune activation in JSLE

Abstract: This study demonstrated significantly increased TLR expression in JSLE compared with controls. Our data indicate that apoptotic neutrophils trigger TLR activation through their presentation of autoantigens. The role of TLRs in this inflammatory response was demonstrated by a dose-response relationship to apoptotic neutrophil concentration and confirmed by a decrease in IFN-α production after inhibition of TLR signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…TLR3 recognizes dsRNA, and its elevated level in human SLE peripheral blood cells suggests that it may play a key role in IFN signature gene activation22464748. In addition, previous research indicated that TLR3 aggravated lupus nephritis in lupus-prone mice68.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR3 recognizes dsRNA, and its elevated level in human SLE peripheral blood cells suggests that it may play a key role in IFN signature gene activation22464748. In addition, previous research indicated that TLR3 aggravated lupus nephritis in lupus-prone mice68.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study of a Mexican population indicated that increased TLR7 copy number correlated with TLR7 mRNA levels and susceptibility to childhood-onset SLE44 although TLR7 copy number variations (CNVs) are infrequent in human SLE45. Other studies indicated that increased expression of TLRs in peripheral blood mononuclear cells and lymphocytes led increased IFN-α expression in SLE patients464748.…”
mentioning
confidence: 99%
“…Gene specific primers for human TLR-7 and TLR-9 and GAPDH genes were selected [17][18][19]. The qPCR reactions were performed in a reaction volume of 20 μL, with 10 μL 2× SensiFAST TM SYBR No-ROX One-Step Mix, 400 nM of each primer, 0.2 μL reverse transcriptase, 0.4 μL RiboSafe RNase inhibitor and 2 μL template.…”
Section: Rna Isolation Reverse Transcription and Quantitative Real-mentioning
confidence: 99%
“…Up-regulation of CXCL10 and subsequent CXCR3-positive Th1 cell response is considered crucial for the T-cellmediated destruction of cells that has classically been seen as the hallmark of TIDM (1719). TLR3 activation has been shown to mediate levels of CXCL10 expression in NIT-1 cultured cells transfected with a synthetic double-stranded RNA (dsRNA) (4), and TLR3 mRNA has been shown to be up-regulated in autoimmune disease in human and animal subjects (9, 20). Therefore, we wanted to investigate if there was a difference in expression of CXCL10 between wild-type (TLR3 +/+ ) and TLR3-deficient (TLR3 / ) NOD mice in the pre-diabetic stage.…”
mentioning
confidence: 99%